Subiektywna ocena stanu zdrowia mieszkańców Tychów (raport z badań) - Kowalczewska-Grabowski, Katarzyna (Chowanna, 2020)
Investigations of social pedagogy are nowadays more and more frequently focused on areas which cover a wider context and go beyond one’s own scientific discipline. There is diagnostic research on recognizing health state of certain social groups or communities. The article presents the research results of subjective assessment of health state of the residents of Tychy. However, it is only a part of a larger project which began in April 2017, whose goal is to create Social and pedagogic model of local diagnosis and social participation in terms of health protection and promotion. The conclusions reached may contribute to actions aimed at increasing the health potential of local communities.